Admixture mapping identifies a locus at 15q21.2-22.3 associated with keloid formation in African Americans - Velez Edwards, Digna R (Hum Genet, 2014)
Keloids are benign dermal tumors that occur ~20-times more often in African versus Caucasian descent individuals. While most keloids occur sporadically, a genetic predisposition is supported by both familial aggregation of some keloids and the large differences in risk among populations. Yet, no well-established genetic risk factors for keloids have been identified. In this study we conducted admixture mapping and whole exome association using 478 African Americans (AAs) samples (122 cases, 356 controls) with exome genotyping data to identify regions where local ancestry associated with keloid risk. Logistic regression was used to evaluate associations under admixture peaks. A significant mapping peak was observed on chr15q21.2-22.3. This peak included NEDD4, a gene previously implicated in a keloid genome-wide association study (GWAS) of Japanese individuals later validated in a Chinese cohort. While we observed modest evidence for association with NEDD4, a more significant association was observed at (myosin 1E) MYO1E. A genome-scan not including the 15q21-22 region also identified associations at MYO7A (p rs35641839, odds ratio [OR]=4.71, 95% confidence interval [CI] 2.38–9.32, p=8.34x10(−6)) at 11q13.5. The identification of SNPs in two myosin genes strongly associated with keloid formation suggests that an altered cytoskeleton contributes to the enhanced migratory and invasive properties of keloid fibroblasts. Our findings support the admixture mapping approach for the study of keloid risk, and indicate potentially common genetic elements on chr15q21.2-22.3 in causation of keloids in AAs, Japanese, and Chinese populations.